The Role of Dendritic Cell Maturation in the Induction of Insulin-Dependent Diabetes Mellitus - Mbongue, Jacques C.; Nieves, Hector A.; Torrez, Timothy W.; Langridge, William H. R. (Frontiers in Immunology, 2017)
Dendritic cells (DCs) are the dominant class of antigen-presenting cells in humans and are largely responsible for the initiation and guidance of innate and adaptive immune responses involved in maintenance of immunological homeostasis. Immature dendritic cells (iDCs) phagocytize pathogens and toxic proteins and in endosomal vesicles degrade them into small fragments for presentation on major histocompatibility complex (MHC) II receptor molecules to naïve cognate T cells (Th0). In addition to their role in stimulation of immunity, DCs are involved in the induction and maintenance of immune tolerance toward self-antigens. During activation, the iDCs become mature. Maturation begins when the DCs cease taking up antigens and begin to migrate from their location in peripheral tissues to adjacent lymph nodes or the spleen where during their continued maturation the DCs present stored antigens on surface MHCII receptor molecules to naive Th0 cells. During antigen presentation, the DCs upregulate the biosynthesis of costimulatory receptor molecules CD86, CD80, CD83, and CD40 on their plasma membrane. These activated DC receptor molecules bind cognate CD28 receptors presented on the Th0 cell membrane, which triggers DC secretion of IL-12 or IL-10 cytokines resulting in T cell differentiation into pro- or anti-inflammatory T cell subsets. Although basic concepts involved in the process of iDC activation and guidance of Th0 cell differentiation have been previously documented, they are poorly defined. In this review, we detail what is known about the process of DC maturation and its role in the induction of insulin-dependent diabetes mellitus autoimmunity.